2019
DOI: 10.1515/biol-2019-0035
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy and Histochemistry of the Roots and Shoots in the Aquatic Selenium Hyperaccumulator Cardamine hupingshanensis (Brassicaceae)

Abstract: The perennial selenium (Se) hyperaccumulator Cardamine hupingshanensis (Brassicaceae) thrives in aquatic and subaquatic Se-rich environments along the Wuling Mountains, China. Using bright-field and epifluorescence microscopy, the present study determined the anatomical structures and histochemical features that allow this species to survive in Se-rich aquatic environments. The roots of C. hupingshanensis have an endodermis with Casparian walls, suberin lamellae, and lignified secondary cell walls; the cortex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 34 publications
2
31
0
Order By: Relevance
“…Lignified phi (Φ) thickenings have been recorded in the inner cortex adjacent to the endodermis in M. milleri [4] and are considered similar to the endodermis in the roots of C. lanceolata , M. glyptostroboides , and other gymnosperm species [9,14,15]. More broadly, lignified Φ thickenings have been reported in the root cortices of several species, including the gymnospermous Ginkgo biloba [13] and C. lanceolata [14], and the angiospermous Pyrus malus [16], Brassica napus , B. oleracea [17,18], Myrica rubra [19], and Cardamine hupingshanensis [20].…”
Section: Introductionmentioning
confidence: 99%
“…Lignified phi (Φ) thickenings have been recorded in the inner cortex adjacent to the endodermis in M. milleri [4] and are considered similar to the endodermis in the roots of C. lanceolata , M. glyptostroboides , and other gymnosperm species [9,14,15]. More broadly, lignified Φ thickenings have been reported in the root cortices of several species, including the gymnospermous Ginkgo biloba [13] and C. lanceolata [14], and the angiospermous Pyrus malus [16], Brassica napus , B. oleracea [17,18], Myrica rubra [19], and Cardamine hupingshanensis [20].…”
Section: Introductionmentioning
confidence: 99%
“…sinense , the adventitious roots, the rhizomes, and the leaf axes all had an endodermis with the following histochemical features; Casparian bands and suberin lamellae surrounded by sclerenchyma layers. These characteristics tend to vary distinctly across tissues and organs in almost all other vascular plants ( Ogura, 1972 ; Fahn, 1990 ; Lersten, 1997 ; Enstone, Peterson & Ma, 2003 ; Evert, 2006 ; Yang et al, 2011 , 2014 , 2019a , 2019b , 2019c , 2020 ; Zhang et al, 2017 ; Zhang, Yang & Seago, 2018 ; Crang, Lyons-Sobaski & Wise, 2018 ; Xiang et al, 2019 ). Displaying alike to A. reniforme var.…”
Section: Discussionmentioning
confidence: 99%
“…and the epiphytic Pleopeltis macrocarpa possess an endodermis and a sclerenchyma layer around the vascular bundles throughout the plant ( Wetzel et al, 2017 ; De los Ángeles Lagoria et al, 2018 ). The endodermis and the sclerenchyma layers support and protect the bodies of vascular plants such as ferns, gymnosperms, and angiosperms ( Fahn, 1990 ; Lersten, 1997 ; Enstone, Peterson & Ma, 2003 ; Evert, 2006 ; Yang et al, 2011 , 2014 , 2019a , 2019b , 2019c , 2020 ; Crang, Lyons-Sobaski & Wise, 2018 ; Zhang et al, 2017 ; Zhang, Yang & Seago, 2018 ; Xiang et al, 2019 ). The presence of these structures suggested that A. reniforme var.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations